Press statement from Press and Publicity Committee (MD 15), 2 May 1926, re: preparations for stoppage
1926-05-02 "Press statement from Press and Publicity Committee (MD 15), 2 May 1926, re: preparations for stoppage" [g0720001.jpg], 2 May 1926, Trades Union Congress TUC Organisation